2018
DOI: 10.1021/acs.biochem.8b00944
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Human Microprocessor on Primary MicroRNAs

Abstract: Single-stranded microRNAs (miRNAs) regulate gene expression by triggering mRNA degradation and/or inhibiting mRNA translation. miRNAs play important roles in various critical cellular processes and are associated with numerous human diseases, including cancer and neurodegenerative diseases. miRNA sequences are embedded in the primary miRNA transcripts (pri-miRNAs) that are initially processed by the Microprocessor complex in the nucleus. Microprocessor can orient itself on pri-miRNAs in two ways: one orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…High-throughput pri-miRNA processing assays. Since DROSHA can cleave either the basal or apical junction of a typical two-junction pri-miRNA 13,14,20,27 , we decided to use the short pri-miRNA substrate, arti1, which contains just one junction, to investigate the substrate recognition ability of DROSHA ( Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High-throughput pri-miRNA processing assays. Since DROSHA can cleave either the basal or apical junction of a typical two-junction pri-miRNA 13,14,20,27 , we decided to use the short pri-miRNA substrate, arti1, which contains just one junction, to investigate the substrate recognition ability of DROSHA ( Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Another part of the pri-miRNA structure is called the basal junction, this is formed between the stem and the 5pbasal and 3p-basal RNA segments [17][18][19] . The stem is sub-divided by DROSHA cleavage sites into the upper and lower stems, and both DROSHA and DGCR8 are coordinated to interact with multiple RNA elements to process pri-miRNA accurately and efficiently 4,5,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microprocessor is a trimetric complex consisting of an RNase III enzyme called DROSHA and a dimer of the RNA-binding protein, DGCR8 [3,[6][7][8][9][10][11] (Fig. S1A).…”
Section: Introductionmentioning
confidence: 99%
“…The apical loop connects to one end of the stem via the apical junction, whereas two ssRNA segments, namely the 5p-and 3p-basal segments, flank the other end, making a basal junction 2,15 . Pri-miRNAs contain several RNA elements, such as UG, UGU, mGHG, CNNC, seedMW, and midMW, which are critical for the efficiency and accuracy of pri-miRNA processing by Microprocessor 8,10,17,[22][23][24][25][26][27][28] . The recent report demonstrated that the internal loop in the lower stem of pri-miRNAs facilitates the single cleavage of pri-miRNAs on the 5p-strand and reduces the double cleavages of Microprocessor, thereby controlling miRNA biogenesis 29 .…”
mentioning
confidence: 99%